ANALYSIS OF GREEN BANKING PRACTICES USING THE ENVIRONMENTAL RISK INDEX AND ITS IMPACT ON THE FINANCIAL PERFORMANCE OF BANKS LISTED ON THE INDONESIAN STOCK EXCHANGE - Amalia Fitri; Chairil Akhyar; Marzuki; Ghazali Syamni (PT. Radja Intercontinental Publishing, 2026)
This study analyzes the effect of green banking practices on the financial performance of banks in Indonesia using the Environmental Risk Index (ERI) as a proxy. Panel data from seven banks listed on the Indonesian Stock Exchange for the period 2018-2024 were analyzed using the Entropy Weight Method and panel data regression. The results of the study reveal specific findings: ERI does not have a significant effect on ROA and NIM, but it has a negative and significant effect on ROE. These findings strongly indicate that the implementation of green banking in Indonesia is still in a transitional phase. The short-term costs arising from sustainability initiatives have been statistically proven to burden the rate of return on equity (shareholder's return), although their impact on asset-based profitability (ROA) and interest margin (NIM) has not yet been observed. This study provides important implications for banks and regulators that sustainability strategies need to be optimized to align with value creation for shareholders.